Kesalahan Penulisan Gairaigo Bahasa Inggris Ke Dalam Bahasa Jepangs - Irfan Saputra; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTGairaigo (loan word) writing errors made by student of Japanese education Riau University academic year 2013/2014 is the background of the author to researching any errors that often arise in the writing gairaigo, what are the possible causes of these errors and is there a difference in student writing ability gairaigo at level I, II and III.Gairaigo writing errors found are students write gairaigo based by English vocabulary or write gairaigo based the way of pronounce that is affected by perception of sound. The next writing errors are errors in the writing of the long vowel, diphthong and katakana writing. This error is probably caused by factors such as students have not mastered the competencies how pronunciation of English vocabulary or influence the way the Indonesian pronunciation pronounce English. Other probably are students forget the katakana or influenced by the way the Indonesian pronunciation pronounce English. The results of this research shows that first year, second year and third year have different capabilities in writing gairaigo.Keyword: gairaigo, fonetic, english, katakana, Riau University.